Preliminary analysis of energy consumption in public buildings with IRAM-ISO 50001 approach. Case study : Faculty of Engineering Oberá - Kerkhoff, Alejandro Javier (2021)
Fil: Kerkhoff, Alejandro Javier. Universidad Nacional de Misiones. Facultad de Ingeniería. Laboratorio de Energías; Argentina.